Perspectives of Kidney Transplant Recipients on eHealth: Semistructured Interviews. Issue 12 (10th November 2022) - Tang, James; Howell, Martin; Roger, Simon; Wong, Germaine; Tong, Allison
Abstract : Background: The acceptability and impact of eHealth on patient outcomes may be limited if their concerns and priorities are not addressed. This study aimed to describe the perspectives and experiences of eHealth among kidney transplant recipients. Methods: Face-to-face semistructured interviews were conducted with 30 adult kidney transplant recipients from New South Wales, Australia (urban and regional), in ambulatory clinics. We used purposive sampling to obtain a wide range of demographic and clinical characteristics. Transcripts were analyzed thematically. Ethics was approved by the Western Sydney Local Health District (6054-2019/ETH08718). Findings: Six themes were identified: seeking access to quality care (prioritizing and trusting clinician advice, better safety and timeliness, enabled by user-friendly content); supporting self-management (responsive to individualized informational need, empowerment through practical knowledge, encouraging connectedness); assessing reliability and trustworthiness (discerning information integrity, applying to own context, apprehensive about privacy and confidentiality); enhancing health system capabilities (synergy with routine consultations, essential to coordination, achieving goals by real-time monitoring); technology burden and limitation (uncertainty with navigation and comprehension, challenged by technical difficulties, requiring additional preparation, confrontation and distress); and lacking applicable value (diminished assurance of medical services, existing practice and procedures, hampered by low expectations and disinterest). Conclusion: Recipients felt eHealth could support healthcare delivery and self-management activities. However, they encountered challenges in navigating technology and were concerned about privacy, confidentiality, and misinformation. eHealth that is accessible, individualized, and secure may improve patient satisfaction and outcomes.